Toward Technologies that Support Family Reflections on Health - Grimes, Andrea; Tan, Desney; Morris, Dan (GROUP '09 Proceedings of the ACM 2009 international conference on Supporting group work, 2009)
Previous research has explored how technology can motivate healthy living in social groups such as friends and coworkers. However, little research has focused on the implications of collecting, sharing, and reflecting upon health information within families. To explore this domain, we conducted a study that consisted of a week-long journaling activity followed by semistructured interviews and formative design activities with 15 families (66 people). We identified four areas in which these practices are unique in a family context. Based on these findings we propose preliminary considerations for technologies that effectively support family reflections on health data.